An acoustic micromixer using low-powered voice coil actuation - Kim, Noori (2020)
A low-powered acoustic micromixer has been presented in this paper. This newly invented system consists of an open-top mixing chamber and a permanent magnet mixer base. A voice coil is attached to the bottom of the mixing chamber with a polydimethylsiloxane membrane. The optimal driving frequency of each mixing test can be co-determined during (or prior to) the mixing via an electrical impedance (Ze) measurement owing to inherent electro-acoustic coupling of the system. When the mixer is driving at its resonance frequency found from the Ze, mixing efficiency is maximized characterizing millie-watt efficiency to achieve a mixing time scale comparable to other acoustic mixers. In addition, the present mixer demonstrates feasibility of a portable microfluidic system, wherein the degree of mixing may be tracked by Ze monitoring from a smart-phone, which may allow each experiment to be controlled remotely over existing network environment. We believe that our study demonstrates a feasible application of microelectromechanical systems technology for the Internet of Things.